Biocompatibility and biomineralization assessment of a new root canal sealer and root-end filling material - Cintra, Luciano Tavares Angelo [UNESP]; Ribeiro, Thiago Alexandre Alves [UNESP]; Gomes Filho, João Eduardo [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Watanabe, Simone [UNESP]; Silva Facundo, Aguinaldo Cândido da [UNESP]; Samuel, Renata Oliveira [UNESP]; Dezan Junior, Eloi [UNESP] (Wiley, 2013)
Objective: This study investigated the short-term subcutaneous tissue reaction and biomineralization ability of two epoxy-based root canal sealers containing calcium hydroxide (MBP and MBPc) and ProRoot MTA. Materials and methods: Polyethylene tubes containing the materials were implanted into the dorsal connective tissue of Wistar rats (n = 52) for 7 or 30 days; empty implanted tubes served as controls. Specimens were stained with hematoxylin-eosin and von Kossa stain or left unstained for observation under polarized light. Qualitative and quantitative evaluations of all tissue reactions were performed. One-way anova and the Kruskal-Wallis test were used for statistical analysis (P < 0.05). Results: No significant differences were observed among the groups. All three materials induced mild-to-moderate tissue reactions at 7 days, which decreased over time. Dystrophic mineralization and birefringent structures were observed only in the ProRoot MTA ® group. Conclusion: Both MBP and MBPc appear to be biocompatible but do not stimulate biomineralization. © 2012 John Wiley & Sons A/S.
Keywords: Biocompatibility; Biomineralization; Mineral trioxide aggregate